The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1464420720951899
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of Pulsed direct current magnetron sputtered titanium nitride thin film using Grey relational analysis

Abstract: Titanium nitride coatings are extensively adopted as an intermediate adhesion layer in the cutting tools because of its superior mechanical properties. The interdependence of each process parameter during the deposition of such a coating process is nonlinear, and hence, it becomes a challenge to determine the output responses without carrying out a wide range of experiments. So to minimize the experiments, Taguchi-based L9 design of experiments were employed in this study with three factors and three levels su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Many studies have been conducted that have shown that the excellent corrosion resistance of titanium and titanium alloys in a wide range of environments is due to the formation of a dense and protective oxide film on the surface of the metal 44 47 , according to the Pourbaix E–pH diagram for titanium in water 48 , 49 , as shown in Fig. 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted that have shown that the excellent corrosion resistance of titanium and titanium alloys in a wide range of environments is due to the formation of a dense and protective oxide film on the surface of the metal 44 47 , according to the Pourbaix E–pH diagram for titanium in water 48 , 49 , as shown in Fig. 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows that the corrosion current on the surface of the two tested titanium alloys was relatively low, and all of the alloys had good corrosion resistance.
Figure 14 Pourbaix E–pH diagram for titanium in water: ( a ) 23 °C 48 and ( b ) 250 °C 49 .
…”
Section: Discussionmentioning
confidence: 99%